Root Morphology of the Maxillary First and Second Molars in an Iranian Population Using Cone Beam Computed Tomography - Zahra Ghoncheh; Behrang Moghaddam Zade; Mohammad Javad Kharazi fard (Frontiers in Dentistry, 2017)
Objectives: This study sought to assess the root morphology and root canal anatomy of the maxillary first and second molars in an Iranian population using cone-beam computed tomography (CBCT). Materials and Methods: Sound fully-developed maxillary first (n=345) and second (n=423) molars were evaluated on 450 CBCT scans ordered for pre-operative assessment for implant placement. The (I) number of roots and their morphology (II) number of canals per root, (III) canal configuration and presence of a second mesiobuccal canal according to the Vertucci’s classification and (IV) unilateral or bilateral occurrence of a second mesiobuccal canal (MB2) were evaluated. Results: Single roots were found in 1.1% of the first and 11.3% of the second molars. Four separate roots were identified in 0.5% of the first molars; none of the second molars had four separate roots. First and second molars showed a higher prevalence of three separate roots of mesiobuccal, distobuccal and palatal with one canal in each root (54% and 86 %, respectively). The most common anatomical variation in the maxillary first molars was related to the configuration of the MB root; the root canal system of the maxillary second molars showed more anatomical variations. Conclusions: Mesiobuccal roots of the maxillary molars had more variations in their canal system than the distobuccal or palatal roots. The root canal configuration of the maxillary second molars was more diverse than that of first molars; CBCT enhances mapping of the mesiobuccal root canal system with the potential to improve the quality of root canal treatment.